HOMOMORPHISM IN ROUGH LATTICE - Dipankar Rana; Sankar Kumar Roy (Journal of New Theory)
− In this paper, we introduce the concept of set-valued homomorphism of a lattice which isthe generalization of ordinary lattice homomorphism. We construct generalized rough lower and upperapproximations operators, by means of a set-valued mapping, which are also the generalized form oflower and upper approximations of a lattice, and the corresponding properties are investigated andfinally we cite an example to show usefulness of the paper